2014
DOI: 10.1007/s12187-014-9271-5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Specific Attachment Relationships of Mother, Father and Peer in Malaysian Adolescents

Abstract: The Inventory of Parent and Peer Attachment (IPPA) is the most widely used self-report measure of individual differences in adolescent attachment. However, the factor structure of this measure has not been replicated outside of the Western adolescent population. Using confirmatory factor analysis (CFA), the aim of this study is to explore the factor structure of the IPPA in Malaysian adolescents. A total of 2,040 school-going adolescents across urban and rural areas of Malaysia completed the 75 items of the IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…By adopting the framework of peer attachment and university adjustment, this study has shown that the hypothesized relationships were partially supported. In addition, following the suggestion made by Ishak, Yunus, and Iskandar (2010) and Zulkefly and Wilkinson (2014) regarding the limited literature exploring the attachment relationship among emerging adults in a non-western samples, this study has made an important empirical contribution to the literature on attachment, particularly in the context of freshmen in Malaysia.…”
Section: Implications and Conclusionmentioning
confidence: 83%
See 3 more Smart Citations
“…By adopting the framework of peer attachment and university adjustment, this study has shown that the hypothesized relationships were partially supported. In addition, following the suggestion made by Ishak, Yunus, and Iskandar (2010) and Zulkefly and Wilkinson (2014) regarding the limited literature exploring the attachment relationship among emerging adults in a non-western samples, this study has made an important empirical contribution to the literature on attachment, particularly in the context of freshmen in Malaysia.…”
Section: Implications and Conclusionmentioning
confidence: 83%
“…There were no past literature to support this notion as this study is the first to examine the effect of peer alienation towards institutional attachment. Nevertheless, Zulkefly & Wilkinson (2014) examined the psychometrics characteristics of IPPA among Malaysian adolescents and found that the original factors of IPPA did not show a replication towards Malaysian culture. They stated that "the understanding towards the attachment concept among young people in Malaysia is different.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, using a sample of 197 college undergraduates from the United States (ages 17–21), researchers replicated the three-factor structure of the mother version of the IPPA, but they were unable to replicate the three-factor structure for peer support (Li et al, 2014). In addition, the original three-factor structure of the IPPA was not replicated in a sample of 2,040 adolescents between the ages of 13 and 17 from Malaysia (Zulkefly & Wilkinson, 2015). Rather, a different three-factor structure for the parental scales was found (Zulkefly & Wilkinson, 2015).…”
Section: Discussionmentioning
confidence: 99%